PENGARUH ALOKASI PAJAK ANTAR PERIODE, PERSISTENSI LABA, DAN LIKUIDITAS TERHADAP KUALITAS LABA DENGAN PROFITABILITAS SEBAGAI MEDIASI - Suryadi, Nanda; Nurani, Ratna; Yusnelly , Arie (Komunitas Manajemen Kompetitif, 2024)
The purpose of this study was to determine the effect of inter-period tax allocation, earnings persistence, and liquidity on earnings quality with profitability as the mediator in food and beverage sub-sector manufacturing companies listed on the bei for the 2019-2021 period. The research data is secondary data obtained from the IDX for the 2019-2021 period. The sample in this study were 34 companies which were taken using the Purposive Sampling method. Data analysis in this study used regression analysis with the help of Smart Pls. The results showed that tax allocation between periods, earnings persistence had no effect on earnings quality. While liquidity affects earnings quality For the results of mediation testing through indirect effect analysis, it is found that the intervening variable (profitability) is not able to mediate the effect of independent variables (inter-period tax allocation, earnings persistence, and liquidity on the dependent variable (earnings quality) Keywords : Profitability, inter-period tax allocation, earnings persistence, liquidity, earnings quality